New alginic acid-atenolol microparticles for inhalatory drug targeting - Ceschan, Nazareth Eliana (2014)
The inhalatory route allows drug delivery for local or systemic treatments in a noninvasively way. The current tendency of inhalable systems is oriented to dry powder inhalers due to their advantages in terms of stability and efficiency. In this work, microparticles of atenolol (AT, basic antihypertensive drug) and alginic acid (AA, acid biocompatible polyelectrolyte) were obtained by spray drying. Several formulations, varying the relative composition AT/AA and the total solid content of the atomized dispersions, were tested. The powders were characterized by: Fourier Transform Infrared Spectroscopy, Differential Scanning Calorimetry and Powder X-ray Diffraction, while also the following properties were measured: drug load efficiency, flow properties,particles size and density, moisture content, hygroscopicity and morphology. The ionic interaction between AA and AT was demonstrated, then the new chemical entity could improve the drug targeting to the respiratory membrane and increase its time residence due to the mucoadhesive properties of the AA polymeric chains. Powders exhibited high load efficiencies, low moisture contents, adequate mean aerodynamic diameters and high cumulative fraction of respirable particles (lower than 10 μm).